Cirurgia ortognática: abordagem psicossocial em pacientes Classe III de Angle submetidos à correção cirúrgica da deformidade dentofacial - Nicodemo, Denise [UNESP]; Pereira, Max Domingues; Ferreira, Lydia Masako (Dental Press Editora, 2007)
AIM: The purpose of this work was to investigate the psychosocial aspects related to facial changes in 29 patients, from both genres, between 17 and 46 years old, with indication of surgical treatment, in the preoperative (during orthodontic preparation) and in the postoperative (six months after the surgery) periods. METHODS: Questionnaires, applied during interviews, with questions based on the proposal by Grossbart & Sarwer were used. The technique of content analysis was used, in which the reason for choosing corrective surgery were represented in Category 1 (C1); fantasies related to the results of the corrective surgery (preoperative) and performance (postoperative) in Category 2 (C2); and expectations and satisfaction of the results of the corrective surgery in Category 3 (C3). The answers were grouped in the subcategories: aesthetics (SC1), functional (SC2), social situations (SC3), self-esteem (SC4) and professional (SC5). RESULTS: the results showed that the patients looked for corrective surgery for functional reasons (34.5%), aesthetics (30.9%) and social (29.1%); wished to improve his/her social situation (40%) and the aesthetics (32%), with the fulfillment of these wishes after the surgery. As for the expectations, 49.4% of the patients hoped to improve the functional aspect followed by aesthetics (26.9%); social situations (11.2%) and self-esteem (6.7%). In all aspects the patients were very satisfied because of improvements in their diction, aesthetics, beauty, and the return to life without discrimination. CONCLUSIONS: It can be concluded that the patients looked for the corrective surgery with the motivation to improve their functional and aesthetics aspects, they fantasized to improve their social relations and appearance; and hoped, in a realistic way, that the corrective surgery would repaired the function and aesthetics - which are the objectives of the orthognathic surgery.

OBJETIVO: investigar aspectos psicossociais relacionados à mudança da aparência facial em 29 pacientes, de ambos os gêneros, com idades entre 17 e 46 anos, com indicação de tratamento cirúrgico, nos períodos pré-operatório (durante preparo ortodôntico) e pós-operatório (transcorridos 6 meses da intervenção cirúrgica). MÉTODOS: utilizou-se questionários, aplicados na forma de entrevistas, com perguntas baseadas na proposta de Grossbart e Sarwer. Utilizou-se a técnica de análise de conteúdo, representando-se o motivo da procura pela correção cirúrgica em Categoria 1 (C1); as fantasias relacionadas aos resultados da correção cirúrgica (pré-operatório) e realização (pós-operatório) em Categoria 2 (C2); e as expectativas e a satisfação quanto aos resultados da correção cirúrgica em Categoria 3 (C3). As respostas foram reagrupadas nas subcategorias: estética (SC1), funcional (SC2), situações sociais (SC3), auto-estima (SC4) e profissional (SC5). RESULTADOS: os resultados indicaram que os pacientes procuraram a correção cirúrgica por motivos funcionais (34,5%), estéticos (30,9%) e sociais (29,1%); desejavam melhorar as situações sociais (40%) e a estética (32%), com realização destes desejos, depois da cirurgia. Quanto às expectativas, 49,4% dos pacientes esperavam melhorar o aspecto funcional, seguido da estética (26,9%), situações sociais (11,2%) e auto-estima (6,7%). Em todos os aspectos, os pacientes ficaram muito satisfeitos pela melhora na dicção, na estética, na beleza e no retorno à vida sem discriminação. CONCLUSÕES: os pacientes procuraram a correção cirúrgica motivados a melhorar o aspecto funcional e a estética; fantasiavam melhorar as relações sociais e a aparência; esperavam, de forma realista, que a correção cirúrgica reparasse a função e a estética - objetivos propostos pela cirurgia ortognática.
Orthognathic surgery: psychosocial approach in Angle Class III patients submitted to correction surgery of facial deformity
Keywords: Plastic surgery; Psychosocial impact; Oral health; Odontologia; Cirurgia plástica; Impacto psicossocial; Saúde bucal